Adjustment of angle error and tolerance allocation methods for RV reducers - ZHANG Bowen; ZHOU Jianxing; CUI Quanwei; LIN Kaihong; ZHOU Yadong; XU Wenqiang (Jixie chuandong)
ObjectiveAiming at the problems that angular errors in key load-bearing components such as crankshafts, cycloidal gears, and pin gear shells during processing and manufacturing lead to the reduction of transmission accuracy and stability of rotary vector (RV) reducers, an angular error adjustment method and a tolerance allocation method for RV reducers based on state space models were proposed.MethodsFirstly, taking the BX40E reducer as the research object, the error transmission chain of the reducer was constructed to illustrate the error transmission path of the RV reducer. Secondly, a state space model of the error transmission process was established. Combining with the optimal control theory and comprehensively considering factors such as transmission accuracy, adjustment man-hour cost, and measurement uncertainty, the optimal adjustment amount for each assembly step and the final error state were given. Finally, with the minimum total processing cost as the objective function, the angular tolerance allocation of key components was completed by using the genetic algorithm.ResultsThe research results prove the effectiveness of this method in improving the transmission accuracy and stability of RV reducers, but different accuracy weight values should be selected according to actual accuracy requirements to minimize costs.